2020
DOI: 10.3390/polym12040949
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characteristics of Wet-Spun Filament Made of Cellulose Nanofibrils with Different Chemical Compositions

Abstract: In this study, wet-spun filaments were prepared using lignocellulose nanofibril (LCNF), with 6.0% and 13.0% of hemicellulose and lignin, respectively, holocellulose nanofibril (HCNF), with 37% hemicellulose, and nearly purified-cellulose nanofibril (NP-CNF) through wet-disk milling followed by high-pressure homogenization. The diameter was observed to increase in the order of NP-CNF ≤ HCNF < LCNF. The removal of lignin improved the defibrillation efficiency, thus increasing the specific surface area and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Several works have reported on the production of lignocellulose nanofibrils (LCNF) from lignin-containing cellulose fibrils (Rojo et al 2015;Imani et al 2019). Lee et al also demonstrated that LCNF with 13% lignin content can be directly wet-spun into fibres by using first tert-butanol and then acetone as coagulants (Park et al 2020). Orelma et al successfully wet-spun LCNF suspensions into fibres using solutions with aluminium sulphate as coagulant, where 50% CMC was added (Orelma et al 2017(Orelma et al , 2019).…”
Section: Lignocellulose and Lcnfmentioning
confidence: 99%
“…Several works have reported on the production of lignocellulose nanofibrils (LCNF) from lignin-containing cellulose fibrils (Rojo et al 2015;Imani et al 2019). Lee et al also demonstrated that LCNF with 13% lignin content can be directly wet-spun into fibres by using first tert-butanol and then acetone as coagulants (Park et al 2020). Orelma et al successfully wet-spun LCNF suspensions into fibres using solutions with aluminium sulphate as coagulant, where 50% CMC was added (Orelma et al 2017(Orelma et al , 2019).…”
Section: Lignocellulose and Lcnfmentioning
confidence: 99%
“…In recent decades, great attention has been paid to fibers from cellulose and its derivatives due to their low cost, light weight, easy processing, good mechanical and barrier properties and recyclability [ 12 ]. It demonstrates great potential in medical material and tissue engineering applications as a functional fiber, due to its superior properties such as biodegradability, thermal stability, biocompatibility and non-toxicity [ 13 , 14 ]. Moreover, CA adequately fulfills a role as structural reinforcement through interactions between polymers and cellulosic materials through hydrogen bonds with amino groups, improving the mechanical properties of the compounds [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the average diameter increased with increasing lignin content, and the filaments from LCNFs showed a rough surface. Park et al [ 34 ] prepared filaments via wet-spinning from PCNF, HCNF, and LCNF suspensions. They also reported that the filaments made of LCNF had a larger diameter with a rougher surface than the filaments made of HCNFs or PCNFs.…”
Section: Resultsmentioning
confidence: 99%
“…The orientation index of the composite filaments was calculated from the azimuthal profiles of the (200) reflections in the 2D XRD patterns, as shown in Figure 6 and summarized in Table 4 . Some studies have reported that the orientation indexes of wet-spun nanocellulose filament were in the range of 0.6–0.8 [ 34 , 35 ], but the orientation indexes of the obtained wet-spun filament made of PCNF/AL and LCNF/AL were in the range of 0.33–0.35. This phenomenon might be due to the gelled AL, which has extremely high viscosity and interferes with the orientation of CNFs in the filament.…”
Section: Resultsmentioning
confidence: 99%